2016
DOI: 10.1002/cctc.201600298
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Metal–Organic Framework Graphene Nanocomposite as a Highly Efficient and Stable Electrocatalyst for the Oxygen Reduction Reaction in Acidic Media

Abstract: We report on the design of a bio‐inspired composite as a noble‐metal‐free electrocatalyst for the oxygen reduction reaction (ORR). The composite is made from the assembly of pyridine‐functionalized graphene (G‐py) and a 3 D metal–organic framework (MOF) deposited onto a glassy carbon electrode (GCE). The 3 D heme‐like MOF was synthesized from tetrakis(4‐carboxyphenyl)porphyrin iron(III) chloride and Zr6 clusters for the assembly of the stable porous coordination network. G‐py, which possesses an axial ligand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Although molecular catalysis by iron porphyrins has provided valuable mechanistic insights into the two‐electron/two‐proton vs. four‐electron/four‐proton reduction of O 2 , a large number of heterogeneous iron‐based materials were reported to act as much better catalysts for electrochemical reduction of O 2 than homogeneous iron complex catalysts . Even better ORR electrocatalytic performance has been reported for a two dimensional (2D) poly‐iron‐phthalocyanine PFe‐Pc, than for the state‐of‐the‐art 20 % platinum/carbon (Pt/C) catalyst in alkaline medium.…”
Section: Iron Complex Catalystsmentioning
confidence: 99%
“…Although molecular catalysis by iron porphyrins has provided valuable mechanistic insights into the two‐electron/two‐proton vs. four‐electron/four‐proton reduction of O 2 , a large number of heterogeneous iron‐based materials were reported to act as much better catalysts for electrochemical reduction of O 2 than homogeneous iron complex catalysts . Even better ORR electrocatalytic performance has been reported for a two dimensional (2D) poly‐iron‐phthalocyanine PFe‐Pc, than for the state‐of‐the‐art 20 % platinum/carbon (Pt/C) catalyst in alkaline medium.…”
Section: Iron Complex Catalystsmentioning
confidence: 99%
“…The results showed that the oxygen reduction was irreversible, and the peak current and the scan rate exhibited an excellent linear relationship, which indicated that the reduction process was adsorption controlled. Furthermore, the stability and recyclability of the PCN‐222‐G‐py electrocatalyst were confirmed by immersing PCN‐222‐G‐py‐GCE in an O 2 ‐saturated 0.5 m H 2 SO 4 solution several times, and the same CVs results were obtained …”
Section: Catalystsmentioning
confidence: 53%
“…Similarly, several other examples of MOFs/graphene (or rGO) composites also exhibited much enhanced electrocatalytic activities for OER or ORR. [ 94–98 ] Besides graphene or rGO, it is also feasible to fabricate MOFs composites with other conductive materials, including activated carbon (AC), [ 99 ] Mxene, [ 100,101 ] CNTs, [ 102–104 ] carbon black, [ 105 ] and Ag nanowires. [ 106 ] The obtained composite usually exhibited greatly enhanced electrocatalytic activities compared with the pure MOF owing to the synergistic effect between the two components that facilitate the electrochemical processes.…”
Section: Pristine Mofsmentioning
confidence: 99%